2018
DOI: 10.3389/fpls.2018.01342
|View full text |Cite
|
Sign up to set email alerts
|

Use of Biostimulants for Organic Apple Production: Effects on Tree Growth, Yield, and Fruit Quality at Harvest and During Storage

Abstract: The experiment was conducted during two consecutive seasons (years 2016 and 2017) in an organic apple orchard of the cultivar Jonathan. Several biostimulants were tested (10 in total), including humic acids, macro and micro seaweed extracts, alfalfa protein hydrolysate, amino acids alone or in combination with zinc, B-group vitamins, chitosan and a commercial product containing silicon. Treatments were performed at weekly intervals, starting from the end of May until mid-August. The macroseaweed extract was ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
44
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 60 publications
8
44
1
4
Order By: Relevance
“…Alfalfa protein hydrolysate and seaweed extracts improved the final coloration and the phenolic concentration in strawberry fruit at harvest (Tables 10 and 11). These results confirm the capacity of both biostimulants to interfere with the phenylpropanoid pathway, leading to more colored and stress-resistant crops [21,27,78,79]. Finally, a reduction in ascorbic acid level in fruits treated with biostimulants containing zinc (ZIN and SIL) was recorded (Table 11).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Alfalfa protein hydrolysate and seaweed extracts improved the final coloration and the phenolic concentration in strawberry fruit at harvest (Tables 10 and 11). These results confirm the capacity of both biostimulants to interfere with the phenylpropanoid pathway, leading to more colored and stress-resistant crops [21,27,78,79]. Finally, a reduction in ascorbic acid level in fruits treated with biostimulants containing zinc (ZIN and SIL) was recorded (Table 11).…”
Section: Discussionsupporting
confidence: 71%
“…Spinelli et al [19] observed the efficacy of seaweed extract in increasing root growth and enhancing tolerance to iron deficiency on strawberry plants, demonstrating that A. nodosum might be a valid substitute of Fe-chelate compounds (e.g., sequestrene). In addition to seaweed extracts, other biostimulant products based on amino acids (such as arginine, glycine, histidine, and phenylalanine) were also found to be able to reduce the negative effects of iron-induced chlorosis and the incidence of physiological disorders in horticultural products (tomato and apple) [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…We noted the largest fruit weight by application of mineral foliar fertilizers in tank mixtures with both studied plant protection systems. We thought that the main reasons were multiple application of nitrogen and amino acid fertilizers which were included in mineral foliar fertilizer system, since this led to the growth and elongation of cells [20]. Such phenomena we observed only on cv.…”
Section: Block Diagrammentioning
confidence: 77%
“…In addition, different concentrations of HA have a significant effect on plant metabolism and plant physiology [26]. Soppelsa et al [27] showed that HA improved apple fruit quality in comparison to different bioregulators. Combined applications of HA and plant growth-promoting bacteria enhanced the yield and quality of organic tomatoes [28].…”
Section: Introductionmentioning
confidence: 99%